Ohmic Contact Properties of Photo-Chemically Etched Nonpolar A-Plane (112¯0) GaN Films. (1st January 2017) - Baik, Kwang Hyeon; Lee, Sohyun; Jang, Soohwan
Abstract : Nonpolar a- plane ( 11 2 ¯ 0 ) GaN ( a- GaN) was photo-chemically etched under ultraviolet illumination using alkali KOH solution, and the Ohmic contact properties on the etched a- GaN epitaxial layer were investigated. After photo-chemical etching, the striated surface morphology along the c- axis [0001] direction was obtained having triangular prisms consisting of m -plane { 10 1 ¯ 0 } facets. The properties of Ti/Al/Ni/Au Ohmic contact on surface-textured a -GaN films were studied with transmission line method patterns aligned along the specific crystal orientations. The minimum specific contact resistance of 9.97 × 10 −5 Ω·cm 2 was achieved along the c- axis on the etched GaN surface at the annealing temperature of 750°C. The etched a- GaN showed higher electrical conductivity along the c- axis than along m- axis. This anisotropic behavior is in contrast to that of the unetched a- GaN where carrier scattering by basal plane stacking faults in the direction perpendicular to the c- axis is a major factor in determining opposite anisotropic conductivity. The higher conductivity along the c-axis of the etched a -GaN film could be explained by more dominant effect of surface roughness scattering.